Early cinema in Scotland - Caughie, John (Edinburgh University Press Ltd, 2018)
Focusing on the social experience of cinema and cinema-going, this collection of essays provides a detailed context for the history of early cinema in Scotland, from its inception in 1896 until the arrival of sound in the early 1930s.